2014
DOI: 10.1186/1472-6920-14-26
|View full text |Cite
|
Sign up to set email alerts
|

Mentorship and pursuit of academic medicine careers: a mixed methods study of residents from diverse backgrounds

Abstract: BackgroundMentorship influences career planning, academic productivity, professional satisfaction, and most notably, the pursuit of academic medicine careers. Little is known about the role of mentoring in recruiting Black/African American and Hispanic/Latino residents into academia. The objective of this study was to assess the influence of mentoring on academic medicine career choice among a cohort of racially and ethnically diverse residents.MethodsA strategic convenience sample of U.S. residents attending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
96
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(101 citation statements)
references
References 32 publications
2
96
0
3
Order By: Relevance
“…3,19 The literature shows that female residents and faculty report a desire for female mentors, and our study results are consistent with this observation. 13,20,21 Gender concordance has been found to lead to better mentorship relationships, 20 but it can be difficult to achieve since females may have more difficulty identifying mentors than their male colleagues (e.g., only 27% of mentors were female in our survey). [21][22][23] Similarly, previous research has shown a tendency for mentees to seek out mentors of the same ethnicity.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…3,19 The literature shows that female residents and faculty report a desire for female mentors, and our study results are consistent with this observation. 13,20,21 Gender concordance has been found to lead to better mentorship relationships, 20 but it can be difficult to achieve since females may have more difficulty identifying mentors than their male colleagues (e.g., only 27% of mentors were female in our survey). [21][22][23] Similarly, previous research has shown a tendency for mentees to seek out mentors of the same ethnicity.…”
Section: Discussionmentioning
confidence: 82%
“…13,20,21 Gender concordance has been found to lead to better mentorship relationships, 20 but it can be difficult to achieve since females may have more difficulty identifying mentors than their male colleagues (e.g., only 27% of mentors were female in our survey). [21][22][23] Similarly, previous research has shown a tendency for mentees to seek out mentors of the same ethnicity. 21 In spite of the potential benefits of gender concordance, others suggest that it is not critical to mentee satisfaction, 7 and previous literature has emphasized shared values, trust, and a personal connection.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Second, although many URM researchers may view racial/ethnic concordance with their mentors as desirable, they acknowledge the reality of the shortage of such mentors in academia. 20 Third, the non-URM mentors from the CNPCs may be experienced with mentoring URM trainees and may not be representative of non-URM mentors in general. Fourth, given that more than one-half of trainees reported having a mentoring team, it is possible that URM trainees in particular may be getting some of their more unique needs met by someone other than their CNPC mentor.…”
Section: Discussionmentioning
confidence: 99%
“…4 Published accounts of current training or mentoring approaches reveal little if any active intervention in regard to the former. 59 …”
Section: The Road Aheadmentioning
confidence: 99%